Large African Bio-Science-based agricultural project targets key famine-type foods and environments - Persley, Gabrielle J. (International Livestock Research Institute, 2011)
Gabrielle Persley pointed out that funding of 10 million US dollars over 5 years will allow projects sponsored by Bio-Innovate to reach the critical mass of financial, agricultural and research resources needed to tackle large-scale regional challenges such as climate change and environmental degradation. In this way Bio-Innovate will help improve food supplies and incomes for small-scale farmers.